Neutrosophic n-SuperHyperNetwork: A New Approach for Evaluating Short Video Communication Effectiveness in Media Convergence - Shouxian Zhu (Neutrosophic Sets and Systems)
This study introduces the Neutrosophic n-SuperHyperNetwork, a graph-based method to evaluate the effectiveness of short video communication in media convergence. By extending the n-SuperHyperGraph with neutrosophic statistics, it models relationships among content creators, platforms, and audiences while addressing uncertain feedback. The paper defines the method, presents its mathematical framework, and compares it with existing graph-based approaches. A detailed case study of a short video campaign on a converged media platform demonstrates its application, with precise calculations showing enhanced accuracy. The findings highlight the method's ability to capture dynamic relationships and uncertainty, offering a valuable tool for media evaluation.